Dear Pandit Jawaharlal Nehru: Goa and the Foundations of the Indian National Liberation Movement - Sandra Ataíde Lobo (Revista Brasileira de História, 2023)
ABSTRACT This paper addresses the understudied early liberation movement in Goa, under the leadership of Tristão de Bragança Cunha (Chandor, 1891-Bombay, 1958), evidencing its building in the intersection of local, national, and international histories, since Cunha achieved the recognition of the Goa Committee in the Indian National Congress. The ideas and views elaborated by Cunha in those years set the core ideas and political basis of the influential wing led by him in Goan nationalism. The study is substantially based on a set of documents, unapproached before, accessed in 2018 at the Nehru Memorial Museum and Archive (New Delhi).